Patterns of thaumarchaeal gene expression in culture and diverse marine environments - Paul Carini; Christopher L. Dupont; Alyson E. Santoro (Environmental Microbiology, 2018)
Summary Thaumarchaea are ubiquitous in marine habitats where they participate in carbon and nitrogen cycling. Although metatranscriptomes suggest thaumarchaea are active microbes in marine waters, we understand little about how thaumarchaeal gene expression patterns relate to substrate utilization and activity. Here, we report the global transcriptional response of the marine ammonia‐oxidizing thaumarchaeon ‘ Candidatus Nitrosopelagicus brevis’ str. CN25 to ammonia limitation using RNA‐Seq. We further describe the genome and transcriptome of Ca . N. brevis str. U25, a new strain capable of urea utilization. Ammonia limitation in CN25 resulted in reduced expression of transcripts coding for ammonia oxidation proteins, and increased expression of a gene coding an Hsp20‐like chaperone. Despite significantly different transcript abundances across treatments, two ammonia monooxygenase subunits ( amoAB ), a nitrite reductase ( nirK ) and both ammonium transporter genes were always among the most abundant transcripts, regardless of growth state. Ca . N. brevis str. U25 cells expressed a urea transporter 139‐fold more than the urease catalytic subunit ureC . Gene coexpression networks derived from culture transcriptomes and 10 thaumarchaea‐enriched metatranscriptomes revealed a high degree of correlated gene expression across disparate environmental conditions and identified a module of coexpressed genes, including amoABC and nirK , that we hypothesize to represent the core ammonia oxidation machinery.